A qualitative analysis of emerging adult black men's sexual decision-making behavior and substance use. Issue 4 (1st October 2016) - Pass, Kenneth M.; Younge, Sinead N.; Geter, Angelica; Al-Bayan, Maliyhah; Wade, Bruce H.
ABSTRACT: Emerging adult Black men and substance users may have an increased risk for compromised sexual health. This study qualitatively investigated how substance use affects the sexual decision-making of emerging adult Black men. Nineteen Black men in college (18–24 years) completed a semi-structured interview about their sexual attitudes, behaviors, and perceptions and their substance use. Results show that substance use may not independently affect sexual risk behavior among emerging adult Black men. Findings highlight the importance of using approaches that incorporate structural and sociocultural factors when framing research and interventions related to substance use, sexual decision making, and Black men.